Job-Related Factors Vis-a-Vis Labour-Management Relations - Jesily, Maria (Prabandhan: Indian Journal of Management, 2013)
The absence of strikes and lockouts does not mean that complete harmony prevails in the labour-management relations. The discontent between the management and the labour is due to some job-related factors. On realizing the importance of this issue, the present study was conducted to assess the existing state of the labour-management relations, to analyze the workers’ perceptions towards the job-related factors and to identify the critical jobrelated factors that affect the labour-management relations adversely. The employeremployee relations in an organization are influenced by both the external as well as the internal factors. The external factors include social, political and economic factors which emanate from outside the purview of the industry over which the management may have little or no control. There are many factors emanating from within the organization such as wages, job interests, working conditions, welfare measures and personnel policies which are referred to as the internal factors. For the purpose of the analysis, the present state of labour-management relations and the perceptions of the workers on various aspects of their jobs were measured through mean scores with the help of a five-point scale. The critical job-related factors which affect the labour management relations adversely were identified and their contribution to the existing state of labour-management relationship was measured by using the intercorrelation matrix and the multiple regression technique. The influence of the independent factors on dependent factors was measured separately and consequently, the critical jobrelated factors were identified. The overall conclusions that emerge from the analysis confirm the fact that the most important factor contributing to the aberrations in labourmanagement relations were the inadequate wages that were paid to an employee for his work, followed by the factor, job insecurity. The workers were dissatisfied with regards to wages and the prospect of job security, and these were found to be the critical job-related factors in affecting the labour-management relations adversely.